From the Spoon to the Town - Jean-Jacques Terrin (In_Bo, 2015)
The famous expression of Ernesto Nathan Rogers well represents an approach that, according to the author, every architect should adopt. Unlike the majority of architects, designers love to build relationships of trust and creativity with the future users of their products and are prone to collaborative work, especially in the field of manual craft and industrial production. Architects should take inspiration from said modus operandi, by adopting cooperative and trans-disciplinary processes, developing participatory approaches and embracing new methods to better manage complexity. By paying more attention to human and anthropological factors and by learning to listen to others, it may be possible to radically revolutionize architectural practices.